Tanap, a new robber fly genus from Turkey (Diptera: Asilidae: Dioctriinae) - Hasbenli̇, Abdullah; Çi̇ftçi̇, Derya; Çağlar, Üzeyi̇r (Zootaxa, 2020)
Tanap gen. nov. and Tanap cinar sp. nov. (Diptera: Asilidae) from Turkey are described and illustrated. This new genus is distinguished from all extant Asilid genera by the presence of projections just behind at the base of the antenna. A key to the Palaearctic genera of Dioctriinae is provided.